Efficacy of a computer-aided detection system in a fecal immunochemical test-based organized colorectal cancer screening program: a randomized controlled trial (AIFIT study) - Rondonotti, Emanuele; Di Paolo, Dhanai; Rizzotto, Erik Rosa; Alvisi, Costanza; Buscarini, Elisabetta; Spadaccini, Marco; Tamanini, Giacomo; Paggi, Silvia; Amato, Arnaldo; Scardino, Giulia; Romeo, Samanta; Alicante, Saverio; Ancona, Fabio; Guido, Ennio; Marzo, Vincenza; Chicco, Fabio; Agazzi, Simona; Rosa, Cesare; Correale, Loredana; Repici, Alessandro; Hassan, Cesare; Radaelli, Franco; on behalf of the AIFIT Study Group (Endoscopy, 2022)
Background Computer-aided detection (CADe) increases adenoma detection in primary screening colonoscopy. The potential benefit of CADe in a fecal immunochemical test (FIT)-based colorectal cancer (CRC) screening program is unknown. This study assessed whether use of CADe increases the adenoma detection rate (ADR) in a FIT-based CRC screening program.Methods In a multicenter, randomized trial, FIT-positive individuals aged 50–74 years undergoing colonoscopy, were randomized (1:1) to receive high definition white-light (HDWL) colonoscopy, with or without a real-time deep-learning CADe by endoscopists with baseline ADR > 25 %. The primary outcome was ADR. Secondary outcomes were mean number of adenomas per colonoscopy (APC) and advanced adenoma detection rate (advanced-ADR). Subgroup analysis according to baseline endoscopists’ ADR (≤ 40 %, 41 %–45 %, ≥ 46 %) was also performed.Results 800 individuals (median age 61.0 years [interquartile range 55–67]; 409 men) were included: 405 underwent CADe-assisted colonoscopy and 395 underwent HDWL colonoscopy alone. ADR and APC were significantly higher in the CADe group than in the HDWL arm: ADR 53.6 % (95 %CI 48.6 %–58.5 %) vs. 45.3 % (95 %CI 40.3 %–50.45 %; RR 1.18; 95 %CI 1.03–1.36); APC 1.13 (SD 1.54) vs. 0.90 (SD 1.32; P  = 0.03). No significant difference in advanced-ADR was found (18.5 % [95 %CI 14.8 %–22.6 %] vs. 15.9 % [95 %CI 12.5 %–19.9 %], respectively). An increase in ADR was observed in all endoscopist groups regardless of baseline ADR.Conclusions Incorporating CADe significantly increased ADR and APC in the framework of a FIT-based CRC screening program. The impact of CADe appeared to be consistent regardless of endoscopist baseline ADR.